Pratinho: de renda extra à comida de rua popular em Fortaleza - Ribeiro, Izakeline de Paiva (2024)
Food culture reflects the traditions and social transformations of a community, especially in dynamic urban centers like Fortaleza. In this context, street food, particularly the pratinho, plays a central role by combining traditional culinary practices with contemporary economic needs. This study examines the economic, social, and cultural dynamics involved in the production and consumption of the pratinho, investigating the motivations of vendors, consumer profiles, and the interactions between these two groups. The dissertation also explores the relationship between street food and the cultural identity of Fortaleza, highlighting how the pratinho both reflects and reinforces local food traditions while adapting to contemporary demands. Through a qualitative approach, including interviews and field observations, the research provides insights into the meanings attributed to the pratinho by both vendors and consumers, revealing how this practice contributes to the local economy and urban socialization. The findings show that pratinho consumption is widespread across Fortaleza's 12 administrative regions, with significant female participation and frequent monthly or weekly consumption. The pratinho transcends its economic function, serving as a bridge between tradition and modernity and establishing itself as a marker of Fortaleza’s identity.